2013
DOI: 10.1093/jjco/hyt115
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Oxaliplatin and Capecitabine and Bevacizumab without Radiotherapy for Poor-risk Rectal Cancer: N-SOG 03 Phase II Trial

Abstract: Objective: This Phase II trial was designed to evaluate the safety and efficacy of neoadjuvant oxaliplatin and capecitabine and bevacizumab without radiotherapy in patients with poor-risk rectal cancer. Methods: Patients with magnetic resonance imaging-defined poor-risk rectal cancer received neoadjuvant oxaliplatin and capecitabine and bevacizumab followed by total mesorectal excision or more extensive surgery. Results: Between February 2010 and December 2011, 32 patients were enrolled in this study. The comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 34 publications
1
88
2
8
Order By: Relevance
“…The preoperative induction of aggressive chemotherapy is anticipated to not only suppress distant metastasis, but to also improve local control in patients with highrisk rectal cancer. The N-SOG03 trial, which evaluated the safety and efficacy of neoadjuvant CAPOX + Bev, showed satisfactory short-term results with a completion rate of 84.4 % and pathological complete response rate of 13.3 % [57]. In this trial, a high rate of Bev-related toxicities, including anastomotic leakage, was a serious problem.…”
Section: Chemotherapy Alonementioning
confidence: 77%
See 1 more Smart Citation
“…The preoperative induction of aggressive chemotherapy is anticipated to not only suppress distant metastasis, but to also improve local control in patients with highrisk rectal cancer. The N-SOG03 trial, which evaluated the safety and efficacy of neoadjuvant CAPOX + Bev, showed satisfactory short-term results with a completion rate of 84.4 % and pathological complete response rate of 13.3 % [57]. In this trial, a high rate of Bev-related toxicities, including anastomotic leakage, was a serious problem.…”
Section: Chemotherapy Alonementioning
confidence: 77%
“…Recently, several studies have been performed to evaluate the safety and efficacy of NAC alone, both in Western countries and Japan ( Several trials have been conducted in Japan to evaluate the safety and efficacy of NAC alone for the treatment of high-risk rectal cancer [57,58]. Upfront surgery is the standard Japanese treatment.…”
Section: Chemotherapy Alonementioning
confidence: 99%
“…The sensitization mechanism of 5‐fluorouracil is to inhibit the thymidylate synthetase 7. For platinum, its mechanism includes radiation‐induced free radicals prompting the formation of toxic platinum intermediates, inhibition of DNA repair, radiation‐induced enhancement of cell platinum absorption, and cell cycle arrest 8, 9. Via redistributing tumor cells into S phase and causing the depletion of the deoxy ATP, gemcitabine can enhance the radio‐sensitivity of tumor radiotherapy 10.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it is often performed with or without molecular targeted drugs for the unresectable or marginally unresectable colorectal cancer to expect that it would be shrunk to be resectable [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%